Marechera’s world: naming people and places in Marechera’s black sunlight - Pfukwa, C.; Maganga, Allan T. (NISC (Pty) Ltd., 2023)
A name is an important statement of identity of a person, persons, a phenomenon, or a place. It can be a peg around which identities are constructed or deconstructed, formed or de-formed, erased or resuscitated, planted or dismembered. The problem of identity is central to Marechera’s concerns, with critics and scholars perpetually trying to place him in certain spaces, sometimes without much success. This article explores Dambudzo Marechera’s Black Sunlight through an onomastic lens, with a view to finding out how the novelist named his characters and space(s) in his story. The names he uses create a landscape that reflects certain forms, processes and patterns. In its analysis of Marechera’s names, the article weaves in current thinking in onomastics and of post-colonial traditions that have influenced literary criticism in the last twenty years.
Keywords: Place naming; People naming; Identity